Can molecular hydrogen supplementation enhance physical performance in healthy adults? A systematic review and meta-analysis - Zhou, Kaixiang; Shang, Zhangyuting; Yuan, Chaoqun; Guo, Zhenxiang; Wang, Yubo; Bao, Dapeng; Zhou, Junhong (Frontiers in Nutrition, 2024)
Background Physical exertion during exercise often leads to increased oxidative stress and inflammatory responses, significantly affecting physical performance. Current strategies to mitigate these effects are limited by their effectiveness and potential side effects. Molecular hydrogen (H₂) has gained attention for its antioxidant and anti-inflammatory properties. Studies have suggested that H2 supplementation contributes to antioxidant potential and anti-fatigue during exercise, but the variance in the observations and study protocols is presented across those studies. Objective This systematic review and meta-analysis aimed to comprehensively characterize the effects of H₂ supplementation on physical performance (i.e., endurance, muscular strength, and explosive power), providing knowledge that can inform strategies using H2 for enhancing physical performance. Methods We conducted a literature search of six databases (PubMed, Web of Science, Medline, Sport-Discus, Embase, and PsycINFO) according to the PRISMA guidelines. The data were extracted from the included studies and converted into the standardized mean difference (SMD). After that, we performed random-effects meta-analyses and used the I2 statistic to evaluate heterogeneity. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to assess the quality of the evidence obtained from this meta-analysis. Results In total, 27 publications consisting of 597 participants were included. The search finally included aerobic endurance, anaerobic endurance, muscular strength, lower limb explosive power, rating of perceived exertion (RPE), blood lactate (BLA), and average heart rate (HRavg) in the effect size (ES) synthesis. The ES of H2 on aerobic endurance, including V̇O2max (SMD = 0.09, p = 0.394; I2 = 0%) and aerobic endurance exercise (SMD = 0.04, p = 0.687; I2 = 0%), were not significant and trivial; the ES of H2 on 30 s maximal anaerobic endurance (SMD = 0.19, p = 0.239; I2 = 0%) was not significant and trivial; the ES of H2 on muscular strength (SMD = 0.19, p = 0.265; I2 = 0%) was not significant and trivial; but the ES of H2 on lower limb explosive power (SMD = 0.30, p = 0.018; I2 = 0%) was significant and small. In addition, H2 reduces RPE (SMD = −0.37, p = 0.009; I2 = 58.0%) and BLA (SMD = −0.37, p = 0.001; I2 = 22.0%) during exercise, but not HRavg (SMD = −0.27, p = 0.094; I2 = 0%). Conclusion These findings suggest that H2 supplementation is favorable in healthy adults to improve lower limb explosive power, alleviate fatigue, and boost BLA clearance, but may not be effectively improving aerobic and anaerobic endurance and muscular strength. Future studies with more rigorous designs are thus needed to examine and confirm the effects of H2 on these important functionalities in humans. Systematic review registration http://www.crd.york.ac.uk/PROSPERO.